A global S. cerevisiae small ubiquitin‐related modifier (SUMO) system interactome. Issue 1 (28th May 2013) - Srikumar, Tharan; Lewicki, Megan C; Raught, Brian
Abstract : The small ubiquitin‐related modifier (SUMO) system has been implicated in a number of biological functions, yet the individual components of the SUMO machinery involved in each of these activities were largely unknown. Here we report the first global SUMO system interactome. Using affinity purification coupled with mass spectrometry, we identify >450 protein–protein interactions surrounding the SUMO E2, Siz type E3s and SUMO‐specific proteases in budding yeast. Exploiting this information‐rich resource, we validate several Siz1‐ and Siz2‐specific substrates, identify a nucleoporin required for proper Ulp1 localization, and uncover important new roles for Ubc9 and Ulp2 in the maintenance of ribosomal DNA. Abstract : A global physical interaction map of the SUMO system was generated to study its functional organization. This resource was used to validate several E3‐specific substrates and uncover novel roles for Ubc9 and Ulp2 in ribosomal DNA maintenance. Synopsis: A global physical interaction map of the SUMO system was generated to study its functional organization. This resource was used to validate several E3‐specific substrates and uncover novel roles for Ubc9 and Ulp2 in ribosomal DNA maintenance. Affinity purification coupled to mass spectrometry was used to construct the first global SUMO interactome in yeast. The analysis identified more than 450 proteins interacting physically with the SUMO E2 Ubc9, the E3 ligases Siz1 and Siz2, and the SUMO‐specific proteases Ulp1 and Ulp2. Several Siz1‐ and Siz2‐specific substrates were validated, such as Cdc12, Sum1, Tup1, Top2, Rpb3 and Spt16. Follow‐up investigations revealed new important roles for Ubc9 and Ulp2 in ribosomal DNA maintenance.